THOC2 and THOC5 Regulate Stemness and Radioresistance in Triple‐Negative Breast Cancer. Issue 24 (27th October 2021) - Bai, Xupeng; Ni, Jie; Beretov, Julia; Wang, Shanping; Dong, Xingli; Graham, Peter; Li, Yong
Abstract: Triple‐negative breast cancer (TNBC) is the most aggressive subtype of breast cancer. Radioresistance and stemness are substantial obstacles to TNBC treatment. The THO complex (THOC) is a subunit of the TRanscription–EXport complex that functions in the coupling of transcription to nascent RNA splicing, elongation, and export. However, its role in regulating TNBC therapeutic resistance is not reported yet. In this study, the authors demonstrate that cancer stem cells are enriched in radioresistant TNBC cells and describe the role of the THOC in regulating TNBC radioresistance and stemness. The authors find that THOC2 and THOC5 are upregulated in radioresistant TNBC cells and associated with a poor prognosis in TNBC patients. Further investigation reveals that THOC2 promotes the stem‐like properties and radioresistance of TNBC cells in a THOC5‐dependent manner by facilitating the release of sex‐determining region Y (SRY)‐box transcription factor 2 (SOX2) and homeobox transcription factor (NANOG) transcripts from the nucleus. Silencing THOC2 or THOC5 expression decreases the protein expression of SOX2 and NANOG, depletes the stem‐like properties, and causes radiosensitization in these TNBC cells. Moreover, THOC2 or THOC5 depletion blocks the xenograft tumorigenesis and growth of radioresistant TNBC in vivo. These findings uncover the novel correlations of THOC with TNBC stemness and therapeutic resistance, proposing alternative therapeutic strategies against relapsed TNBC. Abstract : This study reveals a critical role of the THO complex (THOC) in cancer stemness enhancement by regulating the transnuclear export of pluripotency transcripts, which is a novel mechanism contributing to triple‐negative breast cancer (TNBC) radioresistance. These findings propose THOC2 and THOC5 as novel therapeutic targets for TNBC by eliminating the stem‐like properties of the tumor.